Recent advances in synthesizing metal nanocluster-based nanocomposites for application in sensing, imaging and catalysis - Shang, Li; Xu, Jie; Nienhaus, Gerd Ulrich (Nano today, 2019)
[Display omitted] •Metal nanocluster-based nanocomposites are novel functional materials with many distinct physicochemical properties.•Different strategies have been developed to fabricate composites of metal NCs and many other functional materials.•Metal nanocluster-based nanocomposites show great potential for application in sensing, imaging and catalysis. Metal nanoclusters (NCs) are a type of ultrasmall nanomaterials with unique physicochemical properties. Novel nanocomposites with exciting new and sometimes exotic properties can be created by combination of metal NCs with other functional materials, greatly expanding the range of possible applications. To exploit this potential, intensive research efforts have been made in recent years, resulting in a wide range of metal NC-based nanocomposites. In this review, we systematically summarize different strategies of fabricating nanocomposites and illustrate their application in sensing, imaging and catalysis. A brief outlook on the future development of metal NC-based nanocomposites is also presented.